Epoxy polyurethane composites filled with polyhydroxybutyrate and doxorubicin for the manufacture of bone implants - Lukashevich, S. A.; Rozhnova, R. A.; Galatenko, N. A.; Kozlova, G. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the basis of epoxy polyurethane (EPU) compositions of fillers (polyhydroxybutyrate) (PHB) and doxorubicin), the new biologically active polymer materials that can be used as bone implants are obtained. The effect of fillers on the physical and mechanical properties of the EPU composite materials is studied, and the optimum compositions of PHB to be 0.1 and 0.3 wt. % are determined. The method of IR spectroscopy shows the effect of fillers on the structure of the compositions. By the example of a model reaction of doxorubicin with phenyl glycidyl ether, the possibility of the chemical immobilization of the drug on the EPU carrier is shown.